Libertad de conciencia y culto: una mirada a la realidad colombiana. (2016)
This article analyzes the rights to freedom of conscience and religion in the light of the separation the church and Colombian state, since 1991. Moreover, the religious beliefs and convictions are those of the "being" of a person, integrating their identity, while, the course of everyday life falls into the "doing". This has resulted in the birth of a public censure based on the criteria and action of whom, whether declared or not, has a religious conviction. Therefore, the consciousness, religious beliefs or principles of life, are not elements to be removed, but rather to be put in the exercise of academia, labor, politics and social life and thus deserve all the respect in society in general.